2019
DOI: 10.1111/jocd.13254
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the relationship between inflammatory blood parameters and rosacea and demodex infestation

Abstract: Background Rosacea is a chronic inflammatory disease. Although the etiopathogenesis of the disease has not been established, it is known that inflammation plays a prominent role in the disease. Demodex mites have been thought to have a role in the pathogenesis of rosacea by causing the occurrence of inflammatory lesions. In the literature, many studies have reported that complete blood count (CBC) parameters have been used as diagnostic biomarkers in diseases associated with inflammatory process. Aims The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 11 publications
0
19
2
Order By: Relevance
“…The pathogenesis of rosacea is not well understood. Immune dysfunction [ 87 ], Demodex [ 88 ], ultraviolet radiation exposure [ 89 ], and vascular hyperreactivity [ 90 ] may all play a role in the pathogenesis of rosacea. The pathogenesis and related mechanisms need further exploration to develop more etiological treatment modalities.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of rosacea is not well understood. Immune dysfunction [ 87 ], Demodex [ 88 ], ultraviolet radiation exposure [ 89 ], and vascular hyperreactivity [ 90 ] may all play a role in the pathogenesis of rosacea. The pathogenesis and related mechanisms need further exploration to develop more etiological treatment modalities.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Other parameters such as monocyte lymphocyte ratio (MLR) and thrombocyte lymphocyte ratio (PLR) have also been reported to be used as markers. 8 Macrophages and monocytes are the most important cell types for the secretion of pro-inflammatory and pro-oxidant cytokines in the inflammation region. 9 High-density lipoprotein cholesterol (HDL) has been shown to protect endothelium cells from the negative effects of low-density lipoprotein cholesterol (LDL) and inhibit the oxidation of LDL molecules.…”
Section: Discussionmentioning
confidence: 99%
“…It has been stated that MHR ratio can be used as an indicator marker of metabolic disorders in rosacea patients. Altunisik et al 8 compared NLR, MLR and PLR ratios between rosacea patients and the HCs and reported that they did not find a significant difference between rosacea and HCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets, nucleated cells synthesized from megakaryocytes, play a role in vasoconstriction, hemostasis, vascular endothelial repair, and host defense. Recent studies have shown that atherogenesis formation is also effective in the development of many hematological diseases, tumor growth factor release and metastasis [16,17].…”
Section: Discussionmentioning
confidence: 99%